2004
DOI: 10.2337/diacare.27.10.2382
|View full text |Cite
|
Sign up to set email alerts
|

Atrophy of Foot Muscles

Abstract: OBJECTIVE -Diabetic neuropathy is a length-dependent process that leads to reduced muscle strength and atrophy of leg muscles in some patients. We hypothesized that intrinsic foot muscles are atrophied in diabetic neuropathy and that the degree of atrophy is a measure of motor dysfunction closely related to the neuropathic process.RESEARCH DESIGN AND METHODS -Consecutive cross-sectional magnetic resonance images of the nondominant foot were obtained for stereological determination of the total volume of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
143
3
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(170 citation statements)
references
References 12 publications
13
143
3
11
Order By: Relevance
“…Постоянная травматизация на фоне сниженной способно-сти к заживлению и нарушения микроцирку-ляции способствует образованию трофических язв [2, 7,22].…”
Section: этиология и патогинезunclassified
See 2 more Smart Citations
“…Постоянная травматизация на фоне сниженной способно-сти к заживлению и нарушения микроцирку-ляции способствует образованию трофических язв [2, 7,22].…”
Section: этиология и патогинезunclassified
“…Прогрессирование данного заболевания характеризуется комплексом ос-ложнений: кардиопатия, нефропатия, ретино-патия, тяжелейшим из которых является син-дром диабетической стопы (СДС), обуслав-ливающий большинство ампутаций нижних конечностей [2, 3,7].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Or it may reflect a demyelinating process, which also shows a length-dependent pattern because longer fibres have a higher probability of conduction block due to demyelination. Recent MRI studies have demonstrated the length-dependent pattern or centripetal progression of muscle denervation in both acquired (Andersen et al, 2004;Andreassen et al, 2009) and hereditary (Gallardo et al, 2006;Chung et al, 2008) forms of polyneuropathy. Diabetic patients commonly develop sensory polyneuropathy with distal pain and sensory loss.…”
Section: Polyneuropathymentioning
confidence: 99%
“…Diabetic polyneuropathy also leads to denervation and loss of distal muscles. Andersen and colleagues estimated muscle volumes in patients with long-term diabetic polyneuropathy by using a stereological determination method based on cross-sectional T1-weighted MRI (Andersen et al, 2004). The volume of the intrinsic foot muscles was halved in diabetic patients with chronic neuropathy, in comparison with that of diabetic patients without neuropathy.…”
Section: Polyneuropathymentioning
confidence: 99%